FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS SIKUMANA KOTA KUPANG TAHUN 2012 - YULIANA DAFROYATI (JURNAL INFO KESEHATAN, 2013)
This research aimed to know the factors that affect the amemia occuranceonpregnant mother at Sikumana Primary Health Care. The kind of this research is quantitative with descriptive design to decribe factors that affect the anemia occuranceon pregnant mothers at Sikumana Primary Health Care. The sample of this research was 36 pregnant mothers who came to do Antenatal Care at Sikumana Primary Health Careespecially at KIA klinic. The result of this research showed that based on the pregnant mother’s age factor 18 out of 36 (50%) pregnant mothers suffered anemia were pregnant at the unrisk age that is 20 years old to less than 35 years old (20 years old - < 35 years old); based on the pregnancy age factor 24 out of 36 (67%) pregnant mothers suffered anemia, and the age of their pregnancy was in Trimester III; based on the level of knowledge factor 18 out of 36 (50%) pregnant mothers had low knowledge level; based on the social economy status factor 18 out of 36 (50%) pregnant mothers were in the low social economy status;based on the nutrition intake during pregnancy factor 18 out of 36 (50%) pregnant mothers were in the inadequate nutrition intake; and based on the discipline level of pregnant mother in consuming the Fe tablet factor 36out of 36 (100%) pregnant mothers were indiscipline in consumingit.